Systems Engineering of Tyrosine 195, Tyrosine 260, and Glutamine 265 in Cyclodextrin Glycosyltransferase from Paenibacillus macerans To Enhance Maltodextrin Specificity for 2-O-d-Glucopyranosyl-l-Ascorbic Acid Synthesis - Han, Ruizhi (American Society for Microbiology, 2013)
In this work, the site saturation mutagenesis of tyrosine 195, tyrosine 260 and glutamine 265 in the cyclodextrin glycosyltransferase (CGTase) from Paenibacillus macerans was conducted to improve the specificity of CGTase for maltodextrin, which can be used as a cheap and easily soluble glycosyl donor for the synthesis of 2-O-d-glucopyranosyl-l-ascorbic acid (AA-2G). Specifically, the site-saturation mutagenesis of three sites—tyrosine 195, tyrosine 260, and glutamine 265—was performed, and it was found that the resulting mutants (containing the mutations Y195S [tyrosine → serine], Y260R [tyrosine → arginine], and Q265K [glutamine → lysine]) produced higher AA-2G yields than the wild type and the other mutant CGTases when maltodextrin was used as the glycosyl donor. Furthermore, double and triple mutations were introduced, and four mutants (containing Y195S/Y260R, Y195S/Q265K, Y260R/Q265K, and Y260R/Q265K/Y195S) were obtained and evaluated for the capacity to produce AA-2G. The Y260R/Q265K/Y195S triple mutant produced the highest titer of AA-2G at 1.92 g/liter, which was 60% higher than that (1.20 g/liter) produced by the wild-type CGTase. The kinetics analysis of AA-2G synthesis by the mutant CGTases confirmed the enhanced maltodextrin specificity, and it was also found that compared with the wild-type CGTase, all seven mutants had lower cyclization activities and higher hydrolysis and disproportionation activities. Finally, the mechanism responsible for the enhanced substrate specificity was explored by structure modeling, which indicated that the enhancement of maltodextrin specificity may be related to the changes of hydrogen bonding interactions between the side chain of residue at the three positions (195, 260, and 265) and the substrate sugars. This work adds to our understanding of the synthesis of AA-2G and makes the Y260R/Q265K/Y195S mutant a good starting point for further development by protein engineering.